Method of constructing general solution of the second order linear ordinary differential equations with variable coefficients - Tungatarov, A.; Skakov, А.А. (Ye.A.Buketov Karaganda State University Publishing house, 2014)
In this article new method of constructing general solution of the second order linear ordinary differential equations with variable coefficients is presented. The general solutions of Airy equation, of the second order linear ordinary differential equations with variable coefficients and coefficient ex are constructed by this method. Constructed in explicit form general solutions can be used for solving of the Cauchy problem and of the two point’s boundary value problems for ordinary differential equations with variable coefficients arising in solving various applied problems of science.
Айнымалы коэффициенттері бар екінші ретті сызықты жай дифференциалдық теңдеулердің жалпы шешімдерін құрудың бір əдісі
Об одном способе построения общих решений линейных дифференциальных уравнений второго порядка с переменными коэффициентами
Keywords: the second order; linear ordinary differential equation; variable and singular coefficients; general solution